The Tanggung Jawab Perbankan Dalam Menjaga Kerahasiaan Data Nasabah Ditinjau Dari Undang-Undang No. 10 Tahun 1998 Mengenai Perbankan Pada PT. BANK MANDIRI (Persero), Tbk Di Kota Kupang - Liwe, Juan Truly Page; Nubatonis, Orpa J; Dju Bire, Chatryen M (Law Faculty, Nusa Cendana University, 2024)
The banking sector plays a vital role in mobilizing public funds. The professionalism of banks is essential for fostering trust among customers in their operational responsibilities. Violations of customer data confidentiality are deemed criminal and necessitate appropriate legal responses. A significant case involved a bank employee leaking the account balance information of a PT. Bank Mandiri (Persero), Tbk customer to unauthorized third parties, resulting in customer protests and legal action that culminated in the employee's dismissal. This incident highlighted the bank's inadequate measures in protecting customer data. This study aims to assess the implications of a bank's failure to maintain customer confidentiality and the strategies employed by banks to safeguard such data for customer protection. The research adopts a normative approach, examining written law through various perspectives, including statutory and conceptual frameworks. Primary legal sources include questionnaires, interviews, and observations, while secondary sources comprise relevant literature. Data collection techniques involve reviewing pertinent regulations. The legal analysis focuses on theoretical inquiries into legal principles. The findings indicate that enhancing public trust in banks hinges on the strict adherence to confidentiality obligations. Criminal, civil, and administrative sanctions should be enforced when violations persist despite regulatory non-compliance.